Refrigerated Sea Water System - Triono, Bambang; Saleh, Mochamad; Kabalmay, Revinsyah Nabil Kautsar (Metromedia, 2022)
Almost all existing ships already have a cooling system. For fishing boats, a cooling system is needed to maintain the quality of fish in order to obtain high economic value. There are various types of refrigerants, one of which is the Refrigerated Sea Water (RSW) system. This paper describes the components and workings of the RSW system